β-catenin signaling modulates the tempo of dendritic growth of adult-born hippocampal neurons - Heppt, Jana; Wittmann, Marie-Theres; Schäffner, Iris; Billmann, Charlotte; Zhang, Jingzhong; Vogt-Weisenhorn, Daniela; Prakash, Nilima; Wurst, Wolfgang; Taketo, Makoto Mark; Lie, Dieter Chichung (EMBO Journal, 2020)
In adult hippocampal neurogenesis, stem/progenitor cells generate dentate granule neurons that contribute to hippocampal plasticity. The establishment of a morphologically defined dendritic arbor is central to the functional integration of adult-born neurons. We investigated the role of canonical Wnt/β-catenin signaling in dendritogenesis of adult-born neurons. We show that canonical Wnt signaling follows a biphasic pattern, with high activity in stem/progenitor cells, attenuation in immature neurons, and reactivation during maturation, and demonstrate that this activity pattern is required for proper dendrite development. Increasing β-catenin signaling in maturing neurons of young adult mice transiently accelerated dendritic growth, but eventually produced dendritic defects and excessive spine numbers. In middle-aged mice, in which protracted dendrite and spine development were paralleled by lower canonical Wnt signaling activity, enhancement of β-catenin signaling restored dendritic growth and spine formation to levels observed in young adult animals. Our data indicate that precise timing and strength of β-catenin signaling are essential for the correct functional integration of adult-born neurons and suggest Wnt/β-catenin signaling as a pathway to ameliorate deficits in adult neurogenesis during aging.
CRIS-Team Scopus Importer:2020-09-25
Keywords: adult neurogenesis; aging; dendrite; hippocampus; Wnt signaling